- PENERAPAN TEKNIK MIND MAPPING DALAM LAYANAN BIMBINGAN KLASIKAL UNTUK MENINGKATKAN PERENCANAAN KARIR SISWA KELAS VIII SMP NEGERI 29 SAMARINDA - Luly Ekani; Wahyu Widyatmoko; Rury Muslifar; Nuril Hidayanti (IKIP Siliwangi, 2026)
This study aims to enchance student’s career planning skills through the implementantion of the mind mapping technique in classical guidance services for grade VIII D student’s at SMP Negeri 29 Samarinda. The research employed the Guidance and Counseling Action Research (PTBK) approach, conductes in two cycles consisting of planning, action, observation and reflection phases. The participants were 26 student’s selelcted based on the student needs analysis (AKPD), in which the career planning aspect was identified as the highest priority. Data were collected using a career planning scale and interviews, and analyzed descriptively through both quantitative and qualitative methods. The findings indicated an improvement in the average score 103,07 in the first cycle to 153 in the second cycle, categorized as high. Therefore, it can be concluded that the application of the mind mapping technique within classical guidance services is effective in improving student’s career planning abilities.